Abnormal post operative bleeding in routine ENT surgery - a caution for the young ENT surgeons - Haque, Rojibul; Asad, Md Khalid; Rasel, MA; Aich, Mani Lal (Bangladesh Journal of Otorhinolaryngology, 2010)
Bleeding may complicate many routine ENT procedures. This may result from technical errors, but bleeding associated with coagulopathy may be difficult to control. We report two cases of abnormal post operative bleeding due to coagulopathy, first one admitted on 2nd post operative day after tonsillectomy and second one admitted on 5th post operative day after septoplasty. Case one was diagnosed as a case of Immune Thrombocytopenic Purpura (ITP), and second case was diagnosed later as a case of von Willebrand's Disease. All otolaryngologists should be aware of common bleeding disorders and their treatment. This knowledge will help for appropriate preoperative screening of patients. The most important component of the preoperative assessment is the bleeding history that directs further laboratory evaluation. Key-words: Post operative bleeding, coagulopthy, post tonsillectomy haemorrhage, Immune Thrombocytopenic Purpura (ITP), Von Willebrand's Disease DOI: 10.3329/bjo.v15i1.4309 Bangladesh J of Otorhinolaryngology 2009; 15(1): 35-37